Comparative trends in the status and rights of the illegitimate child (2013)
This study seeks to examine the dual laws on illegitimacy in Nigeria and the changing fortune of the “illegitimate child” from the colonial era to the landmark provisions of section 39(2) of the 1979 Constitution (now section 42(2) of the 1999 Constitution of Nigeria. Although it has been a little over 33 years now since that Constitutional Provision came into effect, there is still much controversy within the academic circle as well as differing judicial decisions of the Courts on its full import and application. Whilst it is generally agreed and fairly settled from judicial 'Interpretation and application that the said Constitutional Provision has abolished the discriminatory practices against the illegitimate child especially in respect of maintenance and inheritance rights, opinions still differ on whether or not that Constitutional Provision has actually abolished the Status of illegitimacy in Nigeria. This study examines the pernicious effect of the common law policy and the unsavoury attitude of the society towards the illegitimate child and makes a case for the abolition of not only the legal incidents of the Status but also the Status itself. Relevant international and regional conventions on the subject as well as the legislative strides of some select developed and developing countries in their quest towards improving the lot of the illegitimate child and establishing legal equality between the legitimate child and the child born out of wedlock are also discussed with a view to highlighting the path to law reform in Nigeria.